Perbandingan Life Skill Ditinjau Dari Model Co-op Co-op Dan Three Steps Interview - Lutfi Arhammuddin; Nurdin Nurdin; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2019)
This study investigated life skills comparison between students who learn using Co-op Co-op models and Three Steps Interview by considering students' self-concept  at Grade X SMK Negeri 1 Seputih Surabaya Academic Year 2018/2019. The purpose of this research was to find out the differences between life skill and the interaction of learning model and students’ self-concept. The method used in this study is comparative experiment. The population of this research was 96 studensts with 64 students as the sample. The technique of this research is used of Random Sampling. In collecting the data, the researcher used sampling  observation and quisionairre. Hypothesis testing using two way variant analysis and two independent sample t-test. Penelitian ini mengkaji tentang perbandingan life skill antara model pembelajaran co-op co-op dan three steps interview dengan memperhatikan konsep diri pada siswa kelas X SMK Negeri 1 Seputih Surabaya Tahun Pelajaran 2018/2019. Tujuan penelitian ini untuk mengetahui perbedaan life skill serta interaksi antara model pembelajaran dan konsep diri siswa. Metode yang digunakan dalam penelitian ini adalah metode komparatif dengan pendekatan eksperimen. Populasi penelitian ini 96 siswa dengan jumlah sampel sebanyak 64 siswa. Teknik penelitian ini adalah Cluster Random Sampling. Teknik pengambilan data dengan observasi, dan angket. Pengujian hipotesis menggunakan rumus analisis varian dua jalan dan t-test dua sampel independen. Kata Kunci : life Skill, co-op co-op, three steps interview, konsep diri